2014
DOI: 10.17221/245/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tillage on physical characteristics in a Mollisol of Northeast China

Abstract: Soil management is aimed at the maintenance of optimal soil physical quality for crop production. In order to explore the effects of tillage practices on soil physical properties, a study was conducted to compare the effects of no tillage (NT), moldboard plow (MP) and ridge tillage (RT) on soil bulk density (BD), soil penetration resistance (SPR), soil water content (SWC), soil macroporosity (MAC) and soil air-filled porosity (AFP) in Northeast China. Results showed that both NT and RT led to significant BD in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Consequently, this improvement facilitated organic matter accumulation and ultimately increased buckwheat yield. Notably, these results align with He's (2015) investigation on light utilisation and alfalfa‐related characteristics.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, this improvement facilitated organic matter accumulation and ultimately increased buckwheat yield. Notably, these results align with He's (2015) investigation on light utilisation and alfalfa‐related characteristics.…”
Section: Discussionsupporting
confidence: 87%
“…Despite a high content of organic carbon, the soils are very weak in soil structure in May when plants and crops start to grow due to the strong freezing and thawing cycles in winter and early spring (Li & Fan, 2014;Ma et al, 2019;Wang et al, 2012). The soil bulk density can change dramatically from 1.01 Mg m À3 (total porosity >64%) in May to 1.40 Mg m À3 in August due to gravity and mechanical compaction during maize cropping (Chen et al, 2014;Jiang et al, 2018). Due to the high clay content, soil water infiltration rate at zero tension was reported to be as low as 25 Â 10 À6 m s À1 in May and August irrespective of the difference in soil bulk density (Jiang et al, 2018).…”
Section: Gully Erosion Rates and Driving Forcesmentioning
confidence: 99%
“…Chen et al [9] observed that NT led to significant BD increment and a significantly lower soil macroporosity than CT at 0-20 cm, while Jabro et al [24] found that ST-IR reduced soil compaction, consequently leading to increased total porosity and lower BD than NT. Similar results were found in our study; significant greater BD in CT-BR, ST-BR, and NT were observed compared to that in ST-IR and CT-IR at a depth of 0-10 cm during the seed emergence period.…”
Section: Effects Of Tillage On Soil Propertiesmentioning
confidence: 99%
“…NT is an important conservation tillage practice, which can be effective in controlling soil erosion, improving soil quality, and reducing input costs and labor needs in this region [3,7]. However, some researchers observed that NT can result in lower crop yields because NT soils with crop residues tend to stay wetter and cooler longer in spring [8,9], which could potentially lead to delay seed germination, impeded root growth, and crop nutrient uptake, and result in reduced yields compared to CT [10][11][12]. Hence, it is hard for local farmers to accept NT as a priority or major pattern of cultivation in farmland.…”
Section: Introductionmentioning
confidence: 99%